Percutaneous coronary intervention with drug‐coated balloon‐only strategy combined with single antiplatelet treatment in patients at high bleeding risk: Single center experience of a novel concept. Issue 3 (22nd January 2023) - Räsänen, Alma; Kärkkäinen, Jussi M.; Eranti, Antti; Eränen, Jaakko; Rissanen, Tuomas T.
Abstract: Objectives: At least 1 month of dual antiplatelet therapy is required after coronary stenting. The aim of this all‐comers retrospective registry study was to assess the efficacy and safety of percutaneous coronary intervention (PCI) using drug‐coated balloon (DCB) with single antiplatelet treatment (SAPT). Methods: Between 2011 and 2020, 232 PCIs were performed in 172 patients using the DCB‐only strategy and discharged with SAPT. Results: The mean age of the patients was 75 ± 11 years and 59% were male. The clinical presentation was stable coronary artery disease (CAD) in 42% of the patients and acute coronary syndrome (ACS) in 58%. The lesions were mainly de novo (96%). The majority (58%) of treated lesions were in large coronary arteries (≥3.0 mm). Most (87%) of the patients were at high bleeding risk (HBR) with at least one major or two minor Academic Research Consortium (ARC) risk factors for bleeding. Periprocedural DAPT was used in 49% of the patients. The 12‐month major adverse cardiac events (MACE, the composition of cardiovascular death, nonfatal myocardial infarction, and target‐lesion revascularization) rate was 1.4% in stable CAD and 7.1% in ACS. The 12‐month all‐cause mortality after DBC only + SAPT strategy was 4.1% in stable CAD and 12.1% in ACS. The rate of ischemia‐driven target lesion revascularisation (TLR) was 0% in stable CAD and 3.0% in ACS at 12 months. The 12‐month rate of significant bleeding (BARC type 2‐5) was 10.5%. There were no acute or subacute vessel closures. Conclusions: Despite the aged patient population with comorbidities, the TLR, MACE, and bleeding rates were low with DCB‐only PCI combined with SAPT. This novel approach could reduce the post‐PCI bleeding risk in patients with CAD and HBR compared to stenting.